The protestant secular in the study of American religion: reappraisal and suggestions. Issue 2 (3rd April 2017) - McCrary, Charles; Wheatley, Jeffrey
ABSTRACT: This article provides a theoretical and historiographical overview of secularism in the study of American religion. It focuses on how scholars have used the concept of the 'Protestant secular' in works on law, politics, and culture. Although it has been useful, we argue that this concept has lost some of its analytical utility in the effort to explain secularism predominantly in terms of its Protestant nature. In turn, this article looks to literature on secularism globally in order to suggest ways forward. Refocusing on secularism as a strategy of state governance ought to bring precision to both 'Protestantism' and 'the secular, ' as well as shift attention toward state power and the high stakes of classification. An analysis of this strategy requires investigation into how states produce and police the category 'religion' and its neighboring concepts – for example, the 'secular' and the 'superstitious' – in order to render, manage, and colonize various populations.